Compensation in Personal Injury Cases: Mean or Median Income? - Leif Danziger; Eliakim Katz (Institute of Labor Economics (IZA), 2019)
Courts typically base compensation for loss of income in personal injury cases on either mean or median work income. Yet, quantatively, mean and median incomes are typically very different. For example, in the US median income is 65 percent of mean income. In this paper we use economic theory to determine the relation between the appropriate make-whole (full) compensation and mean and median work incomes. Given that consumption uncertainty associated with compensation generally exceeds that associated with work income, we show that the appropriate make-whole compensation exceeds mean (and therefore median) work income. Hence, if the compensation must be either the mean or the median work income, then mean work income should be selected.
Keywords: K13; 330; compensation; personal injury; income loss; uncertainty; risk aversion